Redirection Concept of Autonomous Mobile Robot HY-SRF05 Sensor to Reduce The Number of Sensors - Nuryanto Nuryanto; Andi Widiyanto; Auliya Burhanuddin (IAES Indonesia Section, 2017)
The autonomous mobile robot can move around and avoid obstacles in front by itself. The data generated by the sensors is processed using an algorithm and specific methods to determine the movement of the robot. Ultrasonic sensor installed on the Mobile robot with a straight forward position. Ultrasonic sensor can detect the obstacle 30 degrees in front, which creates the blank area of the sensor between two ultrasonic sensors. Ultrasonic sensors installed at many points to reduce that blank area. This paper offers the concept of two ultrasonic sensor redirection by mounting it tilted so when it is drawn will form a right triangle that the concept of trigonometry applied. The results of the approximate distance between the obstacle sensor becomes the hypotenuse, while the distance between the two sensors already obtained so that the distance between the mobile robot with the real obstacle can be calculated. The mechanism of mobile robot movement mimics the movement of agricultural tractors. The test results showed that the optimum angle between the two ultrasonic sensors is 35 to 55 degree. Redirection ultrasonic sensors will reduce approximately 42% of the number of sensors that are installed straight ahead.